Stability of octadecyltrimethoxysilane-based coatings on aluminum alloy surface - Zhizhchenko, Alexey Y.; Shabalina, Anastasiia V.; Aljulaih, Ali A.; Gurbatov, Stanislav O.; Kuchmizhak, Aleksandr A.; Iwamori, Satoru; Kulinich, Sergei A. (Materials)
Long-term stability in contact with water of organosilane layers formed by octadecyltrimethoxysilane (ODTMS) on polished aluminum alloy (AA2024) through dip-coating was studied by combining SEM, water contact angle measurements, and X-ray photoelectron spectroscopy. Similar organosilane layers were formed on AA2024 coated with permanganate conversion coating, 1,2-bis(triethoxysilyl)ethane (BTSE) and hydrated SiOx as under-layers, after which their long-term durability was also tested. During immersion in water for about one month, all the samples exhibited a decrease in hydrophobicity, implying the prepared organosilane layer was not stable over time, gradually hydrolyzing and letting water interact with the underlying layer. In parallel, SEM images of one-layer samples taken after immersion showed clear signs of local electrochemical corrosion, while XPS analysis confirmed a loss of silicon from the surface layer. The highest stability over time was demonstrated by a one-layer sample prepared in an ethanol/water bath for 5 min and by a similar ODTMS layer prepared on hydrated MnOx as an under-layer.